The Association Between Insulin Initiation and Adverse Outcomes After Hospital Discharge in Older Adults: a Population-Based Cohort Study - Lysy, Zoe (J Gen Intern Med, 2019)
BACKGROUND: Starting insulin therapy in hospitalized patients may be associated with an increase in serious adverse events after discharge. OBJECTIVE: Determine whether post-discharge risks of death and rehospitalization are higher for older hospitalized patients prescribed new insulin therapy compared with oral hypoglycemic agents (OHAs). DESIGN: Retrospective population-based cohort study including hospital admissions in Ontario, Canada, between April 1, 2004, and Nov 30, 2013. PATIENTS: Persons aged 66 and over discharged after a hospitalization and dispensed a prescription for insulin and/or an OHA within 7 days of discharge. We included 104,525 individuals, subcategorized into four mutually exclusive exposure groups based on anti-hyperglycemic drug use in the 7 days post-discharge and the 365 days prior to the index admission. MAIN MEASURES: Prescriptions at discharge were categorized as new insulin (no insulin before admission), prevalent insulin (prescribed insulin before admission), new OHA(s) (no OHA or insulin before admission), and prevalent OHA (prescribed OHA only before admission) as the referent category. The primary and secondary outcomes were 30-day deaths and emergency department (ED) visits or readmissions respectively. KEY RESULTS: Of 104,525 patients, 9.2% were initiated on insulin, 4.1% died, and 26.2% had an ED visit or readmission within 30 days of discharge. Deaths occurred in 7.14% of new insulin users, 4.86% of prevalent insulin users, 3.25% of new OHA users, and 3.45% of prevalent OHA users. After adjustment for covariates, new insulin users had a significantly higher risk of death (adjusted hazard ratio (aHR) 1.59, 95% confidence interval (CI) 1.46 to 1.74) and ED visit/readmissions (aHR 1.17, 95% CI 1.12 to 1.22) than prevalent OHA users. CONCLUSIONS: Initiation of insulin therapy in older hospitalized patients is associated with a higher risk of death and ED visits/readmissions after discharge, highlighting a need for better transitional care of insulin-treated patients.